Interaction of bacterial metagenome and virome in patients with cirrhosis and hepatic encephalopathy. Issue 6 (30th September 2020) - Bajaj, Jasmohan S; Sikaroodi, Masoumeh; Shamsaddini, Amirhossein; Henseler, Zachariah; Santiago-Rodriguez, Tasha; Acharya, Chathur; Fagan, Andrew; Hylemon, Phillip B; Fuchs, Michael; Gavis, Edith; Ward, Tonya; Knights, Dan; et al.
Abstract : Objective: Altered bacterial composition is associated with disease progression in cirrhosis but the role of virome, especially phages, is unclear. Design: Cross-sectional and pre/post rifaximin cohorts were enrolled. Cross-sectional: controls and cirrhotic outpatients (compensated, on lactulose (Cirr-L), on rifaximin (Cirr-LR)) were included and followed for 90-day hospitalisations. Pre/post: compensated cirrhotics underwent stool collection pre/post 8 weeks of rifaximin. Stool metagenomics for bacteria and phages and their correlation networks were analysed in controls versus cirrhosis, within cirrhotics, hospitalised/not and pre/post rifaximin. Results: Cross-sectional: 40 controls and 163 cirrhotics (63 compensated, 43 Cirr-L, 57 Cirr-LR) were enrolled. Cirr-L/LR groups were similar on model for end-stage liver disease (MELD) score but Cirr-L developed greater hospitalisations versus Cirr-LR (56% vs 30%, p=0.008). Bacterial alpha/beta diversity worsened from controls through Cirr-LR. While phage alpha diversity was similar, beta diversity was different between groups. Autochthonous bacteria linked negatively, pathobionts linked positively with MELD but only modest phage-MELD correlations were seen. Phage–bacterial correlation network complexity was highest in controls, lowest in Cirr-L and increased in Cirr-LR. Microviridae and Faecalibacterium phages were linked with autochthonous bacteria in Cirr-LR, but not Cirr-L hospitalised patients had greater pathobionts, lower commensal bacteria and phages focused on Streptococcus, Lactococcus and Myoviridae. Pre/post: No changes in alpha/beta diversity of phages or bacteria were seen postrifaximin. Phage–bacterial linkages centred around urease-producing Streptococcus species collapsed postrifaximin. Conclusion: Unlike bacteria, faecal phages are sparsely linked with cirrhosis characteristics and 90-day outcomes. Phage and bacterial linkages centred on urease-producing, ammonia-generating Streptococcus species were affected by disease progression and rifaximin therapy and were altered in patients who experienced 90-day hospitalisations.